Pretreatment and optimisation of oil palm decanter cake for optimised biobutanol production - Abdul Razak, Mohamad Nafis (2013)
Oil palm industry generated massive amount of lignocellulosic biomass that became a major problem in oil palm mills. Oil palm decanter cake (OPDC) is one of the lignocellulosic biomass that was managed by open dumping in the mills. Utilization of OPDC for the production of crude cellulase cocktail, fermentable sugars and biobutanol were a great approach to manage the abundant biomass, thereby adding value to the waste. In this study, the characteristics and pretreatments of OPDC were investigated. The OPDC with high lignin content (30.66% (w/w)) required an appropriate pretreatment prior to cellulase production and saccharification process. Due to pretreatment process using 1% NaOH and autoclaved at 121°C for 20 minutes, the increment of hydrolysis percentage up to 12-fold higher than untreated OPDC was achieved. The lignin percentage was reduced by 14.1% (w/w) and cellulose and hemicellulose percentages increased by 26.6% (w/w) after the pretreatment. Production of crude cellulase cocktail using OPDC as the substrate by Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2 was successfully investigated. The optimum conditions of these fungi to produce high activity of cellulose using untreated OPDC were 120 hours incubation period, 1x107 spores/mL, temperature at 30°C and initial pH of 7.0 -7.5. T. asperellum UPM1 produced 17.53 U/mL CMCase, 0.53 U/mL β-glucosidase and 0.28 U/mL FPase while A. fumigatus UPM2 produced 10.93 U/mL CMCase, 0.76 U/mL β-glucosidase and 0.24 U/mL FPase. The crude cellulase cocktail with the ratio of 1:1 for T. asperellum UPM1 and A. fumigatus UPM2 improved the fermentable sugar concentration from 3.17 g/L (1.27 g/g) to 5.08 g/L (2.03 g/g) and hydrolysis percentage increased from 50.69% to 81.29% compared to the single crude cellulase. Optimization of biobutanol production using OPDC hydrolysate by Clostridium acetobutylicum ATCC824 was evaluated statistically using response surface methodology (RSM). The analysis of variance (ANOVA) using 2-level factorial successfully screened three significant variables that influenced the biobutanol yield which were glucose concentration in OPDC hydrolysate, inoculum size and initial pH value. The batch fermentation analyzed using central composite design (CCD) gave the predicted optimum conditions of 70 g/L OPDC hydrolysate, 16.20% inoculum size and initial pH of 5.2. The predicted yield of biobutanol was 0.09 g/g with 70 g/L utilization of glucose. The optimum condition was validated and the actual biobutanol yield was 0.11 g/g with 6.04 g/L biobutanol concentration. The biobutanol production using synthetic glucose produced 15.38% higher biobutanol concentration compared to OPDC hydrolysate probably due to the presence of inhibitor and impurities during the physiochemical pretreatment of the substrate.